Cosmic tapestry - Yurt, Nasuhi (New Jersey : Everest Production, 2008)
Explores the science of cosmology. Analysing the structures that could help to determine the forces that shape our Galaxy and trigger star formation.
Executive producer, Adem Kalac.
Host : Laura Wells.
Keywords: Cosmology